Glass-coated beryllium mirrors for the LHCb RICH1 detector - Barber, G; Brook, N; Cameron, W; D'Ambrosio, C; Frei, C; Harnew, N; Head, R; Khimitch, Y; Khmelnikov, V; Loveridge, P; Metlica, F; Obraztsov, V; et al. (2007)
The design, manufacture and testing of lightweight glass-coated beryllium spherical converging mirrors for the RICH1 detector of the LHCb experiment are described. The mirrors need to be lightweight to minimize the material budget and fluorocarbon-compatible to avoid degradation in the RICH1 C4F10 gas radiator. Results of the optical measurements for small-sized prototypes and for a full-sized prototype mirror are reported. © 2006 Elsevier B.V. All rights reserved.